Increased DMSP availability during thermal stress influences DMSP-degrading bacteria in coral mucus - Gardner, Stephanie G.; Nitschke, Matthew R.; O’Brien, James; Motti, Cherie A.; Seymour, Justin R.; Ralph, Peter J.; Petrou, Katherina; Raina, Jean-Baptiste (Frontiers in Marine Science, 2022)
Reef-building corals are among the largest producers of dimethylsulfoniopropionate (DMSP), an essential compound in marine biogeochemical cycles. DMSP can be catabolised in coral mucus by a wide diversity of coral-associated bacteria, where it can either be demethylated, leading to the incorporation of sulfur and carbon into bacterial biomass – or cleaved by lyases, releasing the climatically-active gas dimethyl sulfide (DMS). It has been demonstrated that thermal stress increases DMSP concentrations in many coral species, however the effect of increased DMSP availability on coral-associated bacteria has not been explored. Here we performed thermal stress experiments to examine how changes in DMSP availability impact bacterial degradation pathways in the mucus of Acropora millepora. DMSP concentrations increased with temperature, reaching a maximum of 177.3 μM after 10 days of heat stress, which represents the highest concentration of DMSP recorded in any environment to date. Bacterial communities in coral mucus were significantly different from the surrounding seawater, yet they did not vary significantly between temperature or time. However, during thermal stress, when DMSP concentrations increased, a significant increase in the abundance of both the demethylation gene dmdA and the cleavage gene dddP were recorded. Importantly, our results show that for the highest DMSP concentrations recorded (above 30 μM), the cleavage pathway became more abundant than the demethylation pathway. This suggests that under high DMSP concentrations characteristic of heat stress, a larger fraction of the DMSP pool in the coral mucus is likely catabolised through the DMS-producing cleavage pathway.